The Philippines : Toward a Better Investment Climate for Growth and Productivity - World Bank Group (Manila, 2015)
This working paper concerns the growth of investment climate in the Philippines. There are several resounding ideas in areas both positive and negative. The growth potential in the Philippines is considerable. The country has significant natural resources; a large pool of managerial and entrepreneurial talent; and widespread proficiency in English. The Government's Medium Term Development Plan (MTDP), 2005-2010 sets ambitious growth and employment targets. Recognizing the opportunity at hand, the MTDP sets much higher growth targets than recent outcomes. The government aims to raise GDP growth from 6.1 percent in 2004 to 8 percent by 2010; increase investments from 19 percent of GDP to 26 percent; create two million jobs annually by 2010 and reduce the incidence of poverty from 26 percent to 19 percent. Meeting the ambitious growth targets will mean addressing key vulnerabilities that has made the Philippines less attractive to investors. From a long-term perspective, the Philippine growth and social development record could have been better. Reforms have delivered only modest growth. Low institutional quality and poor fiscal conditions lie behind reforms, delivering only modest growth and private investments. The importance of the fiscal and institutional environment is further underscored by the Investment Climate Survey (JCS). A survey of more than 700 firms was conducted jointly by the Asian Development Bank (ADB) and the World Bank between 2003 and 2004. The survey confirmed the broad cross-country analysis. The two biggest impediments to a good investment climate identified by firms were macroeconomic instability and corruption. Electricity supply, security and regulatory uncertainty, all related to institutional quality also figured prominently. A deeper analysis of the aforementioned themes is contained in this working paper.